Identification of Optimal Operating Condition of Six Bus System Based on Reliability Evaluation - Sreeshobha, E; P.V.N.Prasad, Prof. (International Journal of Engineering and Technology, 2018)
Practical Transmission system interconnecting Ramagundam Thermal power plant, Kotagudam thermal power plant and Nagarjunasagar hydal power plant with Hyderabad, Karnool and Gooty load points is considered for present study. This six bus ring system is a part of the Telangana stateÂ  transmission system.Â  Reliability indices of the system for variable load at Hyderabad load bus are obtained. Based on the reliability indices the optimal operating condition of the system is identified. Operating the system at identified optimal operating point will nullify the installation of redundant components and adequacy improving components. Generation outage transmission outage and generation cum transmission outages are the possible contingencies which can occur during the operation of the considered practical composite power system. Telangana state transmission system is simulated for different possible contingencies with Power system simulation for Engineering software tool. Load point and system reliability indices evaluated for twelve different contingency cases. Referring to load point and system reliability indices, optimal operating point of ring system evaluated. Present study will indicate the load magnitude, upper boundary of load magnitude corresponding to reliable operation of the system.Â